Formulasi Cookies Tepung Pisang Raja dan Tepung Kacang Merah sebagai Makanan Selingan Pencegahan Balita Stunting - Audy Zahra Aprilia; Agus Sulaeman; Witri Priawantiputri; Judiono; Widi Hastuti; Gurid Pramintarto Mulyo (Jurusan Gizi Poltekkes Kemenkes Bandung, 2026)
Stunting is a chronic malnutrition condition that impairs child growth and development, commonly caused by nutrient deficiency during the first 1,000 days of life. According to the 2023 Indonesian Health Survey (SKI), 15.8% of children under five were stunted and 5.7% severely stunted. Efforts to reduce stunting include providing supplementary foods rich in protein and zinc, such as cookies formulated with nutrient-dense flours. This study aimed to determine the effect of plantain flour and red bean flour formulations with added catfish flour on the quality of cookies. An experimental design with a Completely Randomized Design (CRD) one-factor model was applied using three treatments: F1 (70%:30%), F2 (50%:50%), and F3 (30%:70%). Sensory evaluation was conducted with 30 semi-trained panelists, and nutrient content was analyzed for protein (Kjeldahl), fat (Soxhlet), carbohydrates (by difference), and zinc (ICP-OES). The results showed formulation F2 was the most preferred by panelists. Kruskal-Wallis analysis revealed significant effects of formulation differences on taste (p=0.006) and overall acceptance (p=0.049). Nutritional composition per 40 g serving was 172.05 kcal energy, 5.82 g protein, 5.74 g fat, 24.27 g carbohydrates, and 0.58 mg zinc, meeting product claims of high protein and zinc source. The estimated selling price per serving was IDR 4,766. Further research is recommended to evaluate the clinical effects of these cookies on improving the nutritional status of stunted children.